Uncertainty and the Double Dividend Hypothesis - Eftichios Sartzetakis; Panagiotis D. Tsigaris (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper examines the double dividend hypothesis in the presence of labour income uncertainty. Empirical evidence shows that uncertainty over labour income is particularly significant in developing, while not negligible in developed countries. Under uncertainty, and assuming incomplete capital markets, the tax system plays a role in providing social insurance and a green tax reform influences its effectiveness. We show that the increase in environmental tax reduces consumption risk while the balanced budget decrease in labour income tax increases income risk. We find that the total welfare effect of a green tax reform differs substantially from the case of certainty. The critical parameters determining the existence of a second dividend are the lump sum transfers, the relative substitutability of the two goods for leisure and the initial tax rates relative to their optimal that determine also the response of labour supply to a change in the tax mix.
Keywords: H21; H23; D62; 330; Double Dividend Hypothesis; Environmental Taxation; Labor Income Taxation; Uncertainty; Tax Incidence Analysis; Ökosteuer; Doppelte Dividende; Lohnsteuer; Steuerinzidenz; Arbeitsangebot; Entscheidung bei Unsicherheit; Theorie